Fat Contents and Fatty Acid Profiles of Indian Scad (Decapterus russelli) - Chrishanthi, E.K.I.; Attygalle, M.V.E. (My University, 2011)
Indian Scad iDecapterus russelli. Sinhala: Linna) is one of the less expensive fish varieties in the Sri Lankan market. Total fat contents in white muscle. red muscle and skin: and fatty acid composition in white muscle of the Indian Scad were evaluated. Tile total fat content was relatively high in the skin (3.64%) and red muscle (3.17%)) while the white muscle contained low amount (0.65%). Fatty ac id profi lcs of white muse Ie showed 32.66% saturated fatty ac ids (SFA). 16.07% monounsaturated fatty acids (M UFA) and 39.38% polyunsaturated fatty acids (PUF A). Among SF A. those occurring in the highest proportions were palmitic acid (C 16:0. 18.36%) and stearic acid (C 18:0. 12.21%). Oleic acid (CI8:1 n-9. 10.61%) and palmotoleic acid (CI6:1 n-T, 3.91%) were the main MUFAs. Eicosapentaenoic acid (EPA. C20:5 n-s, 8.83%) and docosahexaenoic acid (DHA, C22:6 n-3. 19.76%) were the main PUFAs. The PUFA/SFA ratio was 1.21and n-6 In-3 ratio was 0.13. Sum of EPA + DHA was 28.59%. Therefore it can be concluded that although the fat content is low the nutritional value of the fat cor.rained in the white muscle of Indian Scad is high.
Keywords: Fatty acids; Indian scad; Decapterus russelli; EPA; DHA